Keefektifan Kerja Sama Antarlembaga dalam Operasi Pemulihan Bencana Alam Banjir Studi Empirik di Provinsi DKI Jakarta - Rita Rita (Bina Nusantara University, 2014)
Research on the effectiveness of interagency cooperation in recovery operation of natural disaster in DKI Jakarta regions combines between the research of interagency cooperation in disaster context and the research of interagency cooperation in public services. This research is deepened by comparing the perception of governmental organization and Non Governmental Organization (NGO). The aim of this research is to do the empirical test of the relationship of situational factors to interagency processes and outcomes. This research is not only to test the hyphotesis but also to observe the phenomenon in the interagency cooperation. The result of this reasearch shows that the perception of the leader of governmental organization toward communication is higher than the perception of leader of NGO. Cooperation between governmental and NGO within the effort to serve the disaster DKI Jakarta regions becomes a model of partnership interagency cooperation.